PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA KELAS V SD - Laritmas, Nick Selfianus; Ritiauw, Samuel P; Ritiauw, Leonid (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
21st-century education demands the development of students' emotional intelligence as a foundation for academic success and psychological well-being. Preliminary observations at SD Negeri 1 Rumah Tiga revealed that fifth-grade students had low abilities in recognizing their emotions, empathizing, and building positive social relationships due to conventional learning that had not optimally developed social-emotional aspects. This study aims to determine the effectiveness of applying the discovery learning model in social studies to improve students' emotional intelligence. This quantitative research involved 32 fifth-grade students as the sample. The instrument used was an emotional intelligence questionnaire with a 4-point Likert scale with a Cronbach's Alpha reliability value of 0.872. Data collection techniques included questionnaires, observations, and documentation. Data analysis employed the Shapiro-Wilk normality test and N-Gain test. The results showed an increase in mean emotional intelligence scores from 61.25 (pretest) to 78.40 (posttest), with an improvement of 17.15 points. All emotional intelligence indicators improved significantly: self-awareness (60.5% to 77.1%), self-management (58.2% to 75.2%), motivation (64.5% to 82.0%), empathy (56.6% to 74.2%), and social awareness (59.6% to 76.2%). It can be concluded that the discovery learning model effectively improves students' emotional intelligence through systematic learning syntax including stimulation, problem identification, data collection, data processing, verification, and drawing conclusions. This model is recommended as an alternative for social studies learning that comprehensively develops students' cognitive and emotional aspects. ABSTRAK Pendidikan abad ke-21 menuntut pengembangan kecerdasan emosional siswa sebagai fondasi keberhasilan akademik dan kesejahteraan psikologis. Observasi awal di SD Negeri 1 Rumah Tiga menunjukkan rendahnya kemampuan siswa kelas V dalam mengenali emosi diri, berempati, dan menjalin hubungan sosial positif akibat pembelajaran konvensional yang belum optimal mengembangkan aspek sosial-emosional. Penelitian ini bertujuan untuk mengetahui efektivitas penerapan model discovery learning dalam pembelajaran IPS untuk meningkatkan kecerdasan emosional siswa. Penelitian kuantitatif ini melibatkan 32 siswa kelas V sebagai sampel. Instrumen yang digunakan adalah angket kecerdasan emosional skala Likert 4 poin dengan nilai reliabilitas Cronbach's Alpha 0,872. Teknik pengumpulan data meliputi angket, observasi, dan dokumentasi. Analisis data menggunakan uji normalitas Shapiro-Wilk dan uji N-Gain. Hasil penelitian menunjukkan peningkatan skor rata-rata kecerdasan emosional dari 61,25 (pretest) menjadi 78,40 (posttest) dengan peningkatan 17,15 poin. Seluruh indikator kecerdasan emosional meningkat signifikan: kesadaran diri (60,5% menjadi 77,1%), pengelolaan diri (58,2% menjadi 75,2%), motivasi (64,5% menjadi 82,0%), empati (56,6% menjadi 74,2%), dan kepedulian sosial (59,6% menjadi 76,2%). Dapat disimpulkan bahwa model discovery learning efektif meningkatkan kecerdasan emosional siswa melalui sintaks pembelajaran sistematis yang mencakup stimulasi, identifikasi masalah, pengumpulan data, pengolahan data, pembuktian, dan penarikan kesimpulan. Model ini direkomendasikan sebagai alternatif pembelajaran IPS yang mengembangkan aspek kognitif dan emosional siswa secara komprehensif.